A first approach to the management of the incidental catch of the eastern Pacific Mexican tuna fleet - Vaca Rodríguez, Juan Guillermo; Dreyfus León, Michel Jules (HIDROBIOLÓGICA, 2017)
The information registered by the Mexican Tuna Management and Dolphin Protection Program (PNAAPD) observers on board the Mexican tuna vessels was used to make a basic statistical analysis of the incidental catch of the Mexican eastern Pacific fleet, and to evaluate different aspects of the spatial and seasonal closure strategy. Twenty spatial and seasonal units were identified and hierarchically classified by set-type into four categories (explosive, avoidable, preventive and acceptable) based on two criteria: the incidental catch per set and the number of sets. Incidental catch reduction curves were created. Finally, and example of incidental catch reduction was performed for the mahi-mahi (dolphin-fish) Coryphaena hippurus and C. aquisells, considering the reduction percentage of incidental catch and main objective species catch (yellowfin tuna, Thunnus albacares), and the number of spatial and seasonal units closed. Log-sets are the type of sets that contribute with the gratest amount of incidental catch, except for billfishes. Of the five analyzed areas, those located off the coasts of Mexico can be considered as those with lower risk for most of the species incidentally caught throughout the year. The direct strategy for most of the management objectives is to eliminate or reduce the number of log-sets for the Mexican tuna fleet, throughout the whole zone or in specific units, resulting in a significant incidental catch reduction and a minimal effect on the yellowfin catch. The choice among five alternatives, none better than the others, establishing the units to be closed and the order to do so to reduce the incidental catch, rests in the decision-makers, and is a function of their preferences in respects to the different criteria used to evaluate the alternatives.